Answer:
- [tex]\sqrt[3]{8+3\sqrt{21} } + \sqrt[3]{8-3\sqrt{21} }[/tex] = 1
Step-by-step explanation:
Given
- [tex]\sqrt[3]{8+3\sqrt{21} } + \sqrt[3]{8-3\sqrt{21} }[/tex]
To find
- The value of the expression
Solution
Let's rewrite the given as:
- [tex]\sqrt[3]{3\sqrt{21} + 8} - \sqrt[3]{3\sqrt{21} - 8}[/tex]
Let the value is m and the expressions under 3rd roots are a and b, then we have
- a = 3√21 + 8, b = 3√21 - 8
- m = ∛a - ∛b
Cube the both sides:
- m³ = (∛a - ∛b)³
- m³ = a - b - 3[tex]\sqrt[3]{a^2b}[/tex] + 3[tex]\sqrt[3]{ab^2}[/tex]
Simplify in bits:
- a - b = 3√21 + 8 - 3√21 + 8 = 16
- ab = (3√21 + 8)(3√21 - 8) = 9*21 - 64 = 125
- ∛ab = ∛125 = 5
So the expression becomes:
- m³ = 16 - 3[tex]\sqrt[3]{125a} + \sqrt[3]{125b}[/tex]
- m³ = 16 - 15∛a + 15∛b
- m³ = 16 - 15(∛a - ∛b)
- m³ = 16 - 15m
Solve for m:
- m³ + 15m - 16 = 0
- m³ - 1 + 15m - 15 = 0
- (m - 1)(m² + m + 1) + 15(m - 1) = 0
- (m - 1)(m² + m + 16) = 0
- m - 1 = 0, m² + m + 16 = 0
- m = 1 is the only real root, the quadratic equation has no real roots
The answer is 1